Investigation the effect of Zn doping on structural and optical properties of SnO2. (2022) - Meena, Deshraj; Verma, Vinay Kumar; Divya,; Prerna,; Rana, Shilpa
Abstract: Herein, pure and Zn doped SnO2 nanostructures with different Zn-doping (1 wt%, 3 wt%, and 5 wt%), have been prepared by the hydrothermal method. Structural parameters of the prepared samples were measured by the X-ray diffraction (XRD). The obtained XRD results suggest high crystallinity and tetragonal rutile structure of the synthesized nanostructures. Also, the broadening and shifting in the peaks position on doping indicates the successful insertion of Zn ion into SnO2 crystal lattice. Energy Dispersive Spectroscopy (EDS) results confirms the presence of zinc in the Zn doped SnO2 nanostructures. Further, the spectroscopic analysis was also carried out using Raman, UV–visible and Photoluminescence Spectroscopy. All the prepared samples exhibit strong and broad Raman and PL peaks. In addition, the observed optical bandgap of the doped nanostructures is smaller than pure SnO2 nanostructures. The effect of zinc doping on structural and optical properties of SnO2 nanostructures have been studied and correlated.